(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
The book is divided into an introduction, three chapters, and a conclusion. The introduction to the book included a statement of the importance of the study, its desired objectives, the research problem and plan, and the scientific method adopted in it. **The first Part: The impact of the Waqf (Endowment) on the development of water resources in Islamic history, and came in five chapters:** **Chapter One: The Waqf: Its Truth and Purposes:** An understanding terminology approach through Waqf Definition, its legality, pillars, and purposes. **Chapter Two: Water: Its Truth, Its Parts and Purposes:** The researcher reviewed the jurisprudential issues related to water, its divisions and purposes, and linked them to main five Items in Islamic law (religion, personality, mind, beget, and money). Its topics included talking about the definition of water in Maliki school of jurisprudence, and a review of the divisions of water sources in Islamic jurisprudence in terms of particular and generality. **Chapter Three: The ruling on owning water in Islamic jurisprudence in general, and the Malikis from it in particular:** Where the researcher touched on the reality of water Waqf (Endowment) and its purposes, and the extent to which the purposes of the Waqf (Endowment) are achieved.